Autophagy and cardiac diseases: Therapeutic potential of natural products. Issue 1 (23rd September 2020) - Wu, Xiaoqian; Liu, Zumei; Yu, Xi‐Yong; Xu, Suowen; Luo, Jiandong
Abstract: The global incidence of cardiac diseases is expected to increase in the coming years, imposing a substantial socioeconomic burden on healthcare systems. Autophagy is a tightly regulated lysosomal degradation mechanism important for cell survival, homeostasis, and function. Accumulating pieces of evidence have indicated a major role of autophagy in the regulation of cardiac homeostasis and function. It is well established that dysregulation of autophagy in cardiomyocytes is involved in cardiac hypertrophy, myocardial infarction, diabetic cardiomyopathy, and heart failure. In this sense, autophagy seems to be an attractive therapeutic target for cardiac diseases. Recently, multiple natural products/phytochemicals, such as resveratrol, berberine, and curcumin have been shown to regulate cardiomyocyte autophagy via different pathways. The autophagy‐modifying capacity of these compounds should be taken into consideration for designing novel therapeutic agents. This review focuses on the role of autophagy in various cardiac diseases and the pharmacological basis and therapeutic potential of reported natural products in cardiac diseases by modifying autophagic processes.